m6A regulates breast cancer proliferation and migration through stage-dependent changes in Epithelial to Mesenchymal Transition gene expression - Dorgham, Mohammed G.; Elliott, Brittany A.; Holley, Christopher L.; Mansfield, Kyle D. (Frontiers in Oncology, 2023)
While many factors have been implicated in breast cancer progression, effective treatments are still lacking. In recent years, it has become clear that posttranscriptional regulation plays a key role in the aberrant gene expression underlying malignancy and metastasis. For example, the mRNA modification N6-methyladenosine (m6A) is involved in numerous post-transcriptional regulation processes and has been implicated in many cancer types, including breast cancer. Despite intense study, even within a single type of cancer, there is little consensus, and often conflicting results, as to the role of m6A, suggesting other factors must influence the process. The goal of this study was to determine if the effects of m6A manipulation on proliferation and migration differed based on the stage of disease progression. Using the MCF10 model of breast cancer, we reduced m6A levels by targeting METTL3, the main cellular m6A RNA methyltransferase. Knocking down Mettl3 at different stages of breast cancer progression indeed shows unique effects at each stage. The early-stage breast cancer line showed a more proliferative phenotype with the knockdown of Mettl3 while the transformed breast cancer line showed a more migratory phenotype. Interestingly, the metastasized breast cancer cell line showed almost no effect on phenotype with the knockdown of Mettl3. Furthermore, transcriptome wide analysis revealed EMT as the probable pathway influencing the phenotypic changes. The results of this study may begin to address the controversy of m6A’s role in cancer and suggest that m6A may have a dynamic role in cancer that depends on the stage of progression.